UPAYA MENINGKATKAN KUALITAS SUMBER DAYA UMKM MELALUI SOSIALIASASI DIGITAL MARKETING DI DESA KRAMATAGUNG KABUPATEN PROBOLINGGO - Taufikurrahman, Taufikurrahman; Imam M, Alfiandi; Budiman, Arief; Dary, Dary; Siti Saliyah, Fildha Hibatur Rahma; Widya Pramesti, Arin; Ardi Saputri, Amelia Oktavia; Nabila Pramana, Tasya (CV. Era Digital Nusantara, 2022)
Behind the modern technology in the economic field, there are still areas that are lagging behind or experiencing inequality. Such as in the Kramatagung Village area, Bantaran District, Probolinggo Regency. Many SME’s actors still market their products conventionally or from person to person because of the lack of knowledge about the use of the internet and its benefits. The proceeds from these sales are only sufficient to meet daily needs so that the development of SME’s businesses has not been able to increase the scale of production and add jobs. The purpose of this activity is to provide knowledge and understanding of digital marketing to SME’s actors to improve the quality of resources and develop their business, so that SME’s actors can reach consumers more broadly. In the implementation of these community service activities, the methods used are observation, interviews, lectures, discussions, demonstrations and practice. After participating in the digital marketing socialization, it is hoped that SME’s actors can utilize information technology as much as possible to help those who want to develop their business and be able to compete globally with other SME’s actors and can be more active in digital marketing through social media and e-commerce applications to be able to enter the market and reach a wider range of customers. In addition, the progress of Kramatagung Village will be clearly seen when SME’s actors apply the methods we inform you and also the level of the economy in Kramatagung Village will experience significant changes with the digital marketing.